2022
DOI: 10.1007/s10639-022-11416-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of teaching and learning machine learning in K-12 education

Abstract: The increasing attention to Machine Learning (ML) in K-12 levels and studies exploring a different aspect of research on K-12 ML has necessitated the need to synthesize this existing research. This study systematically reviewed how research on ML teaching and learning in K-12 has fared, including the current area of focus, and the gaps that need to be addressed in the literature in future studies. We reviewed 43 conference and journal articles to analyze specific focus areas of ML learning and teaching in K-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…These components included target audience, setting, duration, contents, pedagogical approaches to teaching, and assessment methods. Sanusi et al (2022) reviewed research on teaching machine learning in K-12 from four perspectives: curriculum development, technology development, pedagogical development, and teacher training development. The findings of the study revealed that more studies are needed on how to integrate machine learning into subjects other than computer science.…”
Section: Integration Of Ai Into the K12 Curriculummentioning
confidence: 99%
“…These components included target audience, setting, duration, contents, pedagogical approaches to teaching, and assessment methods. Sanusi et al (2022) reviewed research on teaching machine learning in K-12 from four perspectives: curriculum development, technology development, pedagogical development, and teacher training development. The findings of the study revealed that more studies are needed on how to integrate machine learning into subjects other than computer science.…”
Section: Integration Of Ai Into the K12 Curriculummentioning
confidence: 99%
“…ML provides rich opportunities for K-12 youths to experiment with training data and learning algorithms. Yet, while there are numerous studies that have investigated youths' understanding of machine learning, most have done so from the perspective of having them train models [27], only few studies (e.g., [8,36,38]) have examined what youths can learn by also testing the models they trained. Furthermore, these studies highlight the need for providing scaffolds to support youths in testing their ML models.…”
Section: Introductionmentioning
confidence: 99%
“…However, in K-12 computing education most efforts have centered on having youths train models with less attention given to testing. For instance, recent systematic reviews rarely mention studies that discuss testing in teaching, learning, and assessing ML in K-12 contexts [9,21,25,27]. This is not only an issue in K-12 education but also in undergraduate ML education where testing is not always included as a necessary step for learners to consider in the ML pipeline [11,28].…”
Section: Introductionmentioning
confidence: 99%
“…College students' career planning based on career interest assessment involves a structured approach to exploring potential career paths aligned with their skills, interests, and aspirations [8]. Utilizing career interest assessments, students gain valuable insights into their strengths, preferences, and values, which serve as a foundation for making informed decisions about their future.…”
Section: Introductionmentioning
confidence: 99%